Impact of road traffic emissions on air quality of the Lisbon region - Borrego, C. (2000)
The main purpose of this paper is to present the study of traffic emissions impact on the Lisbon region air quality. Two approaches of emission data generation with high spatial and temporal resolution are presented and compared. Main roads were processed as line sources and hot on-road emissions were calculated based on daily mean traffic and emission factors distinguished for several road classes and vehicle types. Also, the disaggregation of national CORINAIR inventory has been performed on the basis of statistical information of fuel consumption and population density. The comparison of emission data obtained by these two approaches demonstrates a good agreement for total values, but a significant difference for spatial distribution of the data. To ensure completeness of the data, to improve their spatial resolution and also to analyse the impact of the traffic emissions, a combination of the two approaches was applied to generate the emission data used by a photochemical numerical system to simulate the atmospheric circulation and the air pollution pattern in Lisbon under summer meteorological conditions, having different emission scenarios. It was possible to conclude that an air pollution abatement strategy is urgently needed and it should take into account the strong contribution of road traffic emissions to the Lisbon air pollution levels.